Sikap Dan Tanggung Jawab Orang Percaya Dalam Menyikapi Teologi Imanensi - Yonatan Alex Arifianto; Alfons Renaldo Tampenawas; Deice Miske Poluan (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
The view of God which is reasoned logically and rationally brings the concept of God as an experience and not a transcendent person. Therefore, any form of immanence theology cannot be accepted as biblical teaching. Through a literature study approach, it is concluded that the existence of a transcendent and immanent God can counter the principles of immanence theology. God is present and actively participates in the world to give believers rest in the knowledge that no place or situation is too far away to be under God's protective hands. And moreover, God is present supernaturally and transcendentally far beyond human reason and logic, both in the form of religiosity that is built and one's relationship with the world.